2017
DOI: 10.1536/ihj.16-020
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-10a Targets T-box 5 to Inhibit the Development of Cardiac Hypertrophy

Abstract: SummaryThe mechanism of cardiac hypertrophy involving microRNAs (miRNAs) is attracting increasing attention. Our study aimed to investigate the role of miR-10a in cardiac hypertrophy development and the underlying regulatory mechanism.Transverse abdominal aortic constriction (TAAC) surgery was performed to establish a cardiac hypertrophy rat model, and angiotensin II (AngII) was used to induce cardiac hypertrophy in cultured neonatal rat cardiomyocytes. Expression of T-box 5 (TBX5) and miR-10a was altered by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
(36 reference statements)
1
24
0
1
Order By: Relevance
“…More than 1,500 different miRNAs have been identified in human genome, and many of them were proved to be involved in cardiovascular development, function, and development of disease. [5][6][7][8] In the cardiovascular-related miRNAs, miR-208a earned more attention as a heart-enriched miRNA. It was considered as a potential biomarker or therapeutic target for the treatment of heart disease.…”
mentioning
confidence: 99%
“…More than 1,500 different miRNAs have been identified in human genome, and many of them were proved to be involved in cardiovascular development, function, and development of disease. [5][6][7][8] In the cardiovascular-related miRNAs, miR-208a earned more attention as a heart-enriched miRNA. It was considered as a potential biomarker or therapeutic target for the treatment of heart disease.…”
mentioning
confidence: 99%
“…[1][2][3] Ryanodine receptor (RyR) is one family of intracellular Ca 2+ release channels which regulates the release of Ca 2+ from the endoplasmic reticulum or sarcoplasmic reticulum into the cytosol. 4) RyR is the largest known ion channel, in form of homotetramers (approximately 2,200 kDa), each subunit of which is comprised of a large N-terminal cytoplasmic domain, accounting for 4/5 of the protein, that modulates the gating of the channel, and 1/5 proportion being luminal and transmembrane spanning (TM) domains.…”
mentioning
confidence: 99%
“…Carè et al (2007) observed that miR-133a attenuates cardiac remodeling by regulating Akt and its downstream signaling molecules such as Cdc42, Rho-A, and Nelf-A/WHSC2 [14]. MiR-10a [15] and miR-497 [16] exert their antihypertrophic effect by blocking translation of Tbx2 and Sirt4, respectively. MiR-223 directly targets cardiac troponin I-interacting kinase (TNNI3K) and inhibits troponin I (cTnI) phosphorylation in cardiomyocytes, which promotes contractility and accumulation of intracellular Ca 2+ [17].…”
Section: Mirna and Cardiac Hypertrophymentioning
confidence: 99%